Optimalisasi Jaringan Komputer Tanpa Harddisk (Diskless) Pada Laboratorium Jaringan AKN Pacitan - Julianto, Bagus; Nugroho, Kurnianto; Saifullah, Danny Febryan Nur Muhamad (Unit Penelitian, Pengabdian Kepada Masyarakat dan Penjamnan Mutu Akademi Komunitas Negeri Pacitan, 2022)
Diskless technology provides convenience for users in terms of managing large numbers of computers. In the process, a group of computers run the system without using a hard disk, with the PXE method every computer connected to the network can run the system by receiving a cloned image provided by the service provider computer (server). The ability of the network to transfer data and the server to serve clients has a huge impact on the process. Optimization from the network side is done by increasing the network's ability to transmit data from 100 Mbps to 1000 Mbps, besides that improvements are also made from the server side where the use of a core i-7 processor, 8 GB memory, and SSD can provide increased performance. The time required to enter the system is 5 minutes, 20 minutes faster than the previous experiment, which was 25 minutes.